Econometrical assay on the impact of the Flex technology in the Brazilian automobile market - Marcelo Almeida Soares (2008)
Consumption of passenger vehicles in Brazil increased significantly in the decades of 1990 and 2000, generated mainly by economic stabilization and credit expansion. In this sense there was a diversification of the Brazilian fleet, as well as a process of sophistication, marked by the incorporation of technology. The development of the sector caused a significant technological breakthrough that led to the spread of technology called flex in 2003. The aggregation of this technology (flex) caused changes in the consumption pattern of vehicles. The purpose of this study is to present a demand function to identify the variables that influence consumerâs decision. This study used an econometric model based on a multiple regression equation, taking as reference the logit model following the same framework adopted by Ferraz et al. (2001) who were interested in studying the effects of environmental regulation in markets of oligopoly. It was showed in this study that the demand for cars is influenced by the flex technology.